Laboratory Findings Associated with Pulmonary Tuberculosis in Diabetic Patients (Academia Journal of Medicine, 2020)
Background: An epidemic of diabetes is currently, both in developed and developing nations. The seriousness of the association of pulmonary tuberculosis and diabetes mellitus was first noted by the great Arab Physician Avicenna nearly 1000 years ago. The global figure of people with diabetes is projected to rise from the current estimate of 220 million to 300 million in 2025. Subjects and Methods: All type 2 diabetic patients reporting to MVJMC and RH will form the subjects for study. The study conducted over a period of 2 yrs. Adult patients with diabetes mellitus with pulmonary tuberculosis were included while Diabetic patients with extrapulmonary tuberculosis were excluded from the study. Results: LDL: 18% of the patients had an LDL value below 100. 40% of the patients had LDL value between 100 – 120. Only 42% of the patients had LDL values between 120-140. HDL: 22.0% of the patients had an HDL value below 30. 24% of the patients had HDL values between 30 – 40. Only 36.0% of the patients had HDL value between 40-50 and 18% of the patients had an HDL value between 50-60. Triglycerides: 56.0% of the patients had Triglycerides value below 150. 42% of the patients had Triglycerides value between 150 – 199. Only 2.0% of the patients had Triglycerides value between 200-499. Conclusion: Male preponderance of the disease was noted and Peak incidence of the disease was noted in the age groups of 31 – 40 and 41 – 50. The majority of our patients had poorly controlled blood sugars, suggesting that severe hyperglycemia is associated with the development of pulmonary tuberculosis and sputum positivity was more in patients aged ≤ 50 yrs. Early diagnosis and properly monitored treatment regimen is the only time tested answer to this problem.
Keywords: Triglycerides; Mantoux; HBA1C levels; Lowenstein –Jensen medium; Sputum AFB